Fabrication of Biopassive Surfaces Using Poly(2‐alkyl‐2‐oxazoline)s: Recent Progresses and Applications. Issue 19 (6th August 2020) - Trachsel, Lucca; Romio, Matteo; Ramakrishna, Shivaprakash N.; Benetti, Edmondo M.
Abstract: Poly(2‐alkyl‐2‐oxazoline)s (PAOXAs) are emerging among the most promising nonionic alternatives to poly(ethylene glycol)s (PEGs), specifically in the modification and functionalization of biomaterials. Due to their chemical tailorability and robustness, coupled to their relatively easy synthesis, PAOXAs are increasingly applied as adsorbates to generate bioinert surfaces that prevent nonspecific contamination by proteins, cells and bacteria. Passivation of medical devices, sensors and cell‐sensitive platforms with PAOXAs enables a nearly quantitative suppression of nonspecific biological contamination, while biopassivity is maintained over longer incubation times than those recorded for more degradable PEG‐based coatings. Thanks to these unique advantages, surface modification strategies involving PAOXAs are expanding to nanomaterials, especially those applied in the fabrication of nanomedicine and bioimaging tools. Abstract : In this progress report, the most recent studies focusing on the fabrication of biopassive surfaces on biomaterials by applying poly(2‐alkyl‐2‐oxazoline)s (PAOXAs) are critically reviewed.